The analytics of the wage effect of immigration - George J. Borjas (IZA Journal of Migration, 2013)
The theory of factor demand has important implications for the study of the impact of immigration on wages. This paper derives the theoretical implications in the context of a general equilibrium model where the wage impact depends on the elasticity of product demand, the rate at which the consumer base expands as immigrants enter the receiving country, the elasticity of supply of capital, and the elasticity of substitution among inputs of production. The constraints imposed by the theory can be used to check the plausibility of the many contradictory claims that appear throughout the immigration literature.
Keywords: J23; J61; F22; 330; Immigration; Wage impact of immigration; Factor demand theory